The heritability of liability to congenital dislocation of the hip - Atasu, Metin; Akkoyunlu, Ümit; Tokgözoğlu, Nejat; Say, Burhan (The Turkish Journal of Pediatrics, 1972)
The heritability of liability to congenital dislocation of the hip was estimated by analysing one hundred index families. It was found as 49.2 ± 1.6 per cent.